10TH GRADE "SOCIO-ECONOMIC GEOGRAPHY OF THE WORLD" COURSE ON THE TOPIC OF GEOGRAPHY OF WORLD TRANSPORT USING THE STRATEGY “GENEALOGY OF DECISIONS” (“DECISION MAKING”) - Khabibullaeva Muhabbatxan Nomonjonovna; Arabboyev Asliddin Rafikzhan Ogli (Scholar Express Journals, 2023)
This article describes the 10th grade “socio-economic geography of the world” Course on the topic of geography of World transport using the strategy “genealogy of decisions” (“decision making”).
Keywords: method; methodology; decision genealogy